Functionalization of CeO2(1 1 1) by Deposition of Small Ni Clusters: Effects on CO2 Adsorption and O Vacancy Formation. Issue 4 (23rd January 2015) - Hahn, Konstanze R.; Seitsonen, Ari P.; Iannuzzi, Marcella; Hutter, Jürg
Abstract In this study we have used density functional theory calculations to investigate the stability, structure and catalytic properties of Ni clusters supported on CeO2. We have found Ni clusters to be stabilized with increasing cluster size up to ten atoms both as isolated clusters and adsorbed on CeO2(1 1 1). Analysis of the structural properties showed an opening of the Ni particles when deposited on CeO2(1 1 1) indicating facilitated accessibility for reacting molecules. The reactivity of the functionalized surface has been examined on the example of CO2 adsorption and activation and compared to the one on pristine CeO2(1 1 1) and isolated Ni clusters. Furthermore, the effect of Ni cluster deposition on the formation and characteristics of surface and subsurface oxygen vacancies in CeO2 has been investigated. The oxygen vacancy position is found to significantly affect the stability and electronic structure of the Ni/CeO2 system.